LITERATURE REVIEW: POLA ASUH IBU DENGAN STATUS GIZI PADA BALITA - Mario Zinduka; Metti Verawati; Dian Laila Purwaningroom; Saiful Nurhidayat; Siti Munawaroh (Health Sciences Journal, 2022)
Parenting is one of the factors that are closely related to the growth and development of toddlers. Parenting is related to the family's ability to provide time, attention and support for children which includes, providing food, caring for cleanliness, and giving affection will affect the child's physical, mental and social. Nutritional problems are closely related to food security problems at the household level which involve knowledge and behavior that do not support a healthy lifestyle. The purpose of this study was to carry out a literature study on Mother Parenting with Nutritional Status in Toddlers. This research method uses a literature review. The search process through Google Scholar publications, PubMeds, Science Direct, uses the keywords "parenting pattern, mother, nutritional status, toddler". The results of the study in 8 journals as literature reviews found that 6 journals explained that mothers provided democratic or good parenting, 5 journals explained good or normal nutritional status, and 5 journals had a relationship between parenting patterns and nutritional status. Democratic parenting by being realistic about the child's abilities, not expecting excessively that exceeds the child's ability so that the nutritional status of toddlers is normal as a reflection of the level of development and welfare of society in a country and is related to the nutritional status of children in the future. Parenting plays an important role in the nutritional status of children. Good parenting for toddlers will be able to optimize the quality of the nutritional status of toddlers through adequate food and health conditions.